2008
DOI: 10.1111/j.1365-2516.2008.01808.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in haemophilia patients

Abstract: Haemophilia patients may develop cardiovascular diseases, suggesting that their clotting defect does not protect them completely from atherosclerosis and its complications. We aimed to evaluate cardiovascular risk factors and, for the first time, the presence of endothelial dysfunction in middle-aged haemophilia patients. We studied 40 patients with haemophilia A and B (24 with moderate-severe disease and 16 with mild disease), and 40 healthy controls. Flow-mediated dilation (FMD), carotid ultrasound (US) inti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
56
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 32 publications
6
56
0
3
Order By: Relevance
“…25 In humans, several earlier studies analyzed the presence of subclinical atherosclerosis by measuring the carotid and femoral intima media thickness (IMT) in patients with hemophilia or von Willebrand disease. [26][27][28][29] Overall, there was no difference in the mean IMT of either the carotid artery (0.75 mm vs 0.74 mm) or femoral artery (0.75 mm vs 0.79 mm) in patients and age-matched healthy controls. 8 Recently, 2 studies investigated whether hypocoagulability is associated with decreased atherogenesis by evaluating subclinical atherosclerosis and endothelial function in hemophilia patients and in matched unaffected controls.…”
Section: Atherosclerosis In Patients With Hemophiliamentioning
confidence: 84%
“…25 In humans, several earlier studies analyzed the presence of subclinical atherosclerosis by measuring the carotid and femoral intima media thickness (IMT) in patients with hemophilia or von Willebrand disease. [26][27][28][29] Overall, there was no difference in the mean IMT of either the carotid artery (0.75 mm vs 0.74 mm) or femoral artery (0.75 mm vs 0.79 mm) in patients and age-matched healthy controls. 8 Recently, 2 studies investigated whether hypocoagulability is associated with decreased atherogenesis by evaluating subclinical atherosclerosis and endothelial function in hemophilia patients and in matched unaffected controls.…”
Section: Atherosclerosis In Patients With Hemophiliamentioning
confidence: 84%
“…[17][18][19][20][21] Srámek et al 21 and Sartori et al 20 found no differences in IMT, whereas 3 other studies [17][18][19] did show a lower IMT, fewer atherosclerotic plaques, or both in hemophilia patients. In these studies, patients were relatively young; mean age ranged from 40 to 58 years.…”
Section: Discussionmentioning
confidence: 89%
“…A major disadvantage in most studies is the heterogeneous study population, combining patients with severe, moderate, and mild hemophilia A or B or von Willebrand disease. 17,18,20,21 Clotting factors VIII and IX and von Willebrand factor play different roles in the development of atherosclerosis. 12,34 Combining these disorders in 1 study might result in masking a possible relationship between 1 of the disorders and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations